Saturation of gain in In0.02Ga0.98N/In0.16Ga0.84N MQW plasmas - Kyhm, K; Taylor, R; Ryan, J; Someya, T; Arakawa, Y (2002)
A new way of analysing the data in a variable stripe length method gain experiment is presented. The stripe length dependence of the gain is measured in In0.02Ga0.98N/In0.16Ga0.84N multiple quantum wells (MQWs). We confirm that this arises from the change of the chemical potential along the excited stripe due to the interaction of the carrier and photon densities, and the gain threshold density is estimated. Comparison with the PL and PLE spectra suggests that the optical gain arises from weakly localised states in the quantum well in our low-indium-content sample. (C) 2002 Elsevier Science B.V. All rights reserved.